P16.28 Solitary fibrous tumor / Hemangiopericytoma: treatment results based on 2016 WHO classification. (19th April 2017) - Sung, K.; Moon, J.; Kim, E.; Chang, W.; Kang, S.; Kim, S.; Kim, S.; Lee, K.; Chang, J.
Abstract: Purpose: Solitary fibrous tumor / hemangiopericytoma (SFT/HPC) is a new combined entity for introduction of a soft tissue-type grading system from grade I to III in the 2016 World Health Organization (WHO) Classification of tumors of the central nervous system. The treatment results of this new disease entity need to be evaluated. We retrospectively reevaluated the pathologic findings and medical records of SFT/HPC. Materials and Methods: This study consisted of 60 patients (27 men and 33 women, 43.5 (13-69) years of age) treated at our institute between February 1981 and February 2016. SFT/HPC grade I, II, and III consisted of 4, 40, and 16 patients, respectively. Among them, there were 7 patients of solitary fibrous tumor and they were re-graded as grade I (n=4), grade II (n=2), and grade III (n=1). Results: Mean overall survival was 79.4 (1.4-275.7) months and progression free survival after first operation was 56.9 (1.4-217.7) months. Six patients (10%) showed extracranial metastasis and median period to extracranial metastasis was 103.7 ± 51.4 (31.9-182.3) months. Nineteen patients (31.6%) presented recurrence. Grade III group had shorter progression free survival, overall survival, and period to extracranial metastasis than grade II group. In grade II group, total resection group showed longer progression free survival than subtotal resection group. However, there was no difference in overall survival. The patients who had adjuvant radiation therapy after surgery had some benefit of longer progression free survival, compared to the patients without adjuvant radiation therapy. Conclusion: SFT/HPC grade I group showed relatively benign course than other groups. The long-term follow-up and periodic systemic evaluation is mandatory to detect systemic metastasis. Grade III group presented more aggressive nature, compared to grade II group. In grade II group, extent of resection and adjuvant radiation therapy is significant for longer progression free survival.